Autoantibody Cancer Biomarker: Extracellular Protein Kinase A - Nesterova, Maria V.; Johnson, Natalie; Cheadle, Christopher; Bates, Susan E.; Mani, Sridhar; Stratakis, Constantine A.; Kahn, Islam; Gupta, Rishab K.; Cho-Chung, Yoon S. (Cancer research (Chicago, Ill.), 2006)
In cancer cells, cyclic AMP–dependent protein kinase (PKA) is secreted into the conditioned medium. This PKA, designated as extracellular protein kinase A (ECPKA), is markedly up-regulated in the sera of patients with cancer. The currently available tumor markers are based on the antigen determination method and lack specificity and sensitivity. Here, we present an ECPKA autoantibody detection method for a universal biomarker that detects cancer of various cell types. We tested sera from 295 patients with cancers of various cell types, 155 normal controls, and 55 patients without cancer. The specificity and sensitivity of this autoantibody enzyme immunoassay method were compared with the conventional antigen determination method by receiver-operating characteristic plots. In the sera, the presence of autoantibody directed against ECPKA was highly correlated with cancer. High anti-ECPKA autoantibody titers (frequency, 90%; mean titer, 3.0) were found in the sera of patients with various cancers, whereas low or negative titers (frequency, 12%; mean titer, 1.0) were found in the control group. The receiver-operating characteristic plot showed that autoantibody enzyme immunoassay exhibited 90% sensitivity and 88% specificity, whereas the enzymatic assay exhibited 83% sensitivity and 80% specificity. These results show that the autoantibody method distinguished between patients with cancer and controls better than the antigen method could. Our results show that autoantibody ECPKA is a universal serum biomarker for cancers of various cell types. (Cancer Res 2006; 66(18): 8971-4)